Slice regular functions in several variables - Ghiloni, Riccardo; Perotti, Alessandro (Mathematische Zeitschrift, 2022)
In this paper, we lay the foundations of the theory of slice regular functions in several (non-commuting) variables ranging in any real alternative ∗ -algebra, including quaternions, octonions and Clifford algebras. This higher dimensional function theory is an extension of the classical theory of holomorphic functions of several complex variables. It is based on the construction of a family of commuting complex structures on R 2 n . One of the relevant aspects of the theory is the validity of a Cauchy-type integral formula and the existence of ordered power series expansions. The theory includes all polynomials and power series with ordered variables and right coefficients in the algebra. We study the real dimension of the zero set of polynomials in the quaternionic and octonionic cases and give some results about the zero set of polynomials with Clifford coefficients. In particular, we show that a nonconstant polynomial always has a non empty zero set.